Gestão pública de megaeventos esportivos no Brasil: a experiência paulistana na realização da Copa do Mundo FIFA - Reis, Rafael Murta (2016)
The research is intended to study public government conducts during the 20th Edition of the FIFA World Cup, occurred in Brazil in 2014. The sports mega-event was surrounded by contradictions, and was publicly contested by thousands of Brazilians, especially with regards to the high amount of public spending and FIFA's (Fédération Internationale de Football Association) considerable profits. During the preparations and the event, Brazil experienced one of the longest cycle of contention in its recent history, highlighting the feeling of dissatisfaction held by many Brazilians with regards to the expenses incurred by federal, state and municipal governments in order to host the games. Focusing mainly on the mega-event management in the city of São Paulo, the study sought to understand the agreement between the parties, and analyze the relationship between the institutions – FIFA and Governments – in the operationalization and decisions regarding the mega-event. Moreover, the study highlights the interfaces established between governments and the civil society, with its empirically identified diversity, and the impacts of its claims on São Paulo's municipal government management. Results show the emergence of antagonistic relations between such groups of interest as well as between different social actors. Additionally, the World Cup in Brazil did not present optimal levels of transparency and public participation, even though some efforts towards these goals were identified. Finally, some of the consequences of the public protests on governmental action can be seen through the use of violence and repression by the police in order to deal with a scenario of multiple protests. Since this study is unique, the research was conducted by qualitative methods. Multiple sources were used during the gathering process which turned possible data triangulation and increased results validity. Direct observations were made during the protests and at the World Cup enterprises’ influence zone. Also official documents, legislations, minutes and press news were analyzed and interviews were conducted with key-actors from federal and municipal governments, activists, protestors, communities’ leaders and society delegates. The survey showed that mega sporting events are an important research topic around the world, and have shown to be a relevant concern in developing countries, as well as have become an important policy tool for promoting the image of host countries overseas and the projection of parties in national territories. Their results highlight the formation of antagonist fields between governments and civil society, and the formation of conflict arenas also among the social actors. Although there have been seen some efforts for the transparency of management, one could not say that the World Cup in Brazil has had ideal level of transparency, neither of social participation. On the one hand there have had efforts to improve transparency, on the other the social participation channels set have not expressed relevance to public management of the mega event. The interfaces between governments and civil society have been identified, as well as their effects and inflections on the management of the World Cup. The main interface highlighted occurred at street level and expressed itself in the confrontations between demonstrators and police. The second most obvious one was consolidated in direct negotiation between communities that were vulnerable to the works of the World Cup and municipal managers. The effects of street protests on the action of governments stood out in police activity, using violence and repression as the main response to the demonstrations, which became most evident in the protests “There Will Not Be World Cup”, and the creation of spaces for direct negotiation with communities, this one influenced more directly by the formation of claim groups, such as the People's Committee of the World Cup, and resistance by the community. The World Cup management in Brazil was complex and showed in the perspective of federative relations some problems between city, state and union, which deals with the coordination of programs, policies or actions, in this case, a mega sports event, of shared management. The case clearly showed dissonances and misalignments between federal, state and municipal government on the practices of dialogue, negotiation, transparency and social participation. The research highlights the formation of a more watchful, critical and politicized social group, which claims, disputes and occupies the streets demonstrating their dissatisfaction with governments, political systems and forms of representation. Points to more tangible results and more harmonious relations between governments and population when alternative forms of social participation and involvement are implemented, particularly spaces and processes where there is room for negotiation and inclusion of civil society in decision-making